2019
DOI: 10.1093/ee/nvz050
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Ecology and Management of Black Turpentine Beetle (Coleoptera: Curculionidae)

Abstract: The black turpentine beetle, Dendroctonus terebrans Olivier is the largest pine-infesting bark beetle native to the southern and eastern United States. It generally reproduces in fresh stumps and bases of trees weakened or killed by other biotic or abiotic agents, although it can also infest and sometimes kills apparently healthy trees. Its numbers can build when large amounts of host material become available (typically through a disturbance), and black turpentine beetle-caused mortality at a local scale can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 144 publications
0
7
0
Order By: Relevance
“…Dendroctonus frontalis and sympatric D. terebrans often share the same host trees, but they exploit different portions and likely compete minimally (Nebeker, 2011). Selection of the same trees is likely mediated in part by shared or cross‐attractive pheromone components (frontalin and endo ‐brevicomin from D. frontalis , and frontalin and exo ‐brevicomin from D. terebrans ) (Munro et al, 2019; Payne et al, 1987; Phillips et al, 1989; Sullivan, 2016) and host odours attractive to both species ( alpha ‐pinene, beta ‐pinene and 4‐allylanisole) (Munro et al, 2020). In experiment 1, responses of both D. terebrans and D. frontalis increased in a similar dose‐dependent manner when 4‐allylanisole was added to bark beetle pheromone components and alpha ‐pinene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dendroctonus frontalis and sympatric D. terebrans often share the same host trees, but they exploit different portions and likely compete minimally (Nebeker, 2011). Selection of the same trees is likely mediated in part by shared or cross‐attractive pheromone components (frontalin and endo ‐brevicomin from D. frontalis , and frontalin and exo ‐brevicomin from D. terebrans ) (Munro et al, 2019; Payne et al, 1987; Phillips et al, 1989; Sullivan, 2016) and host odours attractive to both species ( alpha ‐pinene, beta ‐pinene and 4‐allylanisole) (Munro et al, 2020). In experiment 1, responses of both D. terebrans and D. frontalis increased in a similar dose‐dependent manner when 4‐allylanisole was added to bark beetle pheromone components and alpha ‐pinene.…”
Section: Discussionmentioning
confidence: 99%
“…This combination was used to attract all three beetle species of interest. Frontalin is the major attractive pheromone component for D. frontalis and D. terebrans and an attractive kairomone for T. dubius , and both endo ‐ and exo ‐brevicomin are pheromone components for D. frontalis and D. terebrans , respectively, that can be attraction enhancers for both species (Munro et al, 2019; Sullivan, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the black turpentine beetle D . terebrans has 36 associated mites ( Munro et al 2019 ), many of which presumably are also found on D. terebrans in the LLPE. In general, arthropods may be predators, parasitoids, competitors, commensals, symbionts, and more in their interactions with other arthropods.…”
Section: Arthropod Interactionsmentioning
confidence: 99%
“…Bark beetles also serve as major prey species for many insectivores, particularly for woodpeckers (Bonnot et al 2009;Saab et al 2014). In addition, bark beetles have fascinating ecological relationships with various fungal species (Munro et al 2019).…”
Section: Historic Backgroundmentioning
confidence: 99%